An Experimental Study on Indigenous Pest Management of White Grub Pest in Ginger Fields - Dympep, A.; Kharbamon, B.; Challam, L. L. (International Journal of Economic Plants, 2025)
The current study was conducted during April, 2024–November, 2024, at West Jaintia Hills district of Meghalaya with the aim of documenting and validating the ITKs followed by the tribal farmers for pest management in ginger fields. Indigenous Technical Knowledge (ITK) derived from traditional wisdom was an asset of farmers in developing countries. However, many of these ITKs were lostdue to lack of documentation and no validation for further improvement with modern scientific technologies. Present-day circumstances made it imperative for indigenous innovations to be evaluated and popularized. Documentation and preservation of Indigenous Technical Knowledge (ITK) was urgently required for a number of different communities, many of which were on the verge of extinction. Many of the farmers practiced the application of soaked tobacco leaves and creation of scarecrows in paddy fields. Further, on validation of ITK method using salt to prevent white grub pest in ginger fields, it was found that percentage of pest infestation was about 5.8% while infestation was lesser in experimental plots using recommended scientific method (4.5%). However, the percentage for pest infestation was highest in case of farmers’ field where no pest control measure was taken. Remarkably, there was not much difference in the yield of ginger in case of both the controlled and experimental plots. Therefore, it could be concluded that the ITKs, which have been used by farmers for centuries, if organized and used scientifically, could also be effective in the creation of eco-friendly, location-specific, economically viable and socially acceptable technologies.